Mass-spring modelling of vault springboard contact - Harwood, M. J. (University Loughborough, 2010)
Vaulting is a discipline in Men's and Women's Artistic Gymnastics. While the springboard contact is not judged, the success of the rest of the vault is underpinned by it. The purpose of this study was to develop an understanding of the mechanics of the springboard contact phase of gymnastic vaulting. An analysis of hopping in place, forward hopping and running jumps on a force platform showed that the force-mass centre displacement relationship during ground contact approximated that of a mass rebounding on a linear spring. Subsequently, two mass-spring models were developed using a symbolic mathematics package. Both models represented the gymnast as a rigid cylinder, with personalized linear and angular inertia characteristics, connected at its mass centre to a linear spring. A one spring model combined the springiness of the gymnast and the springboard in a single linear spring, while a two spring model treated them as separate linear springs. Handspring vaults performed by an elite male gymnast at a range of approach speeds and springboard settings were analysed to provide model inputs. Springboard properties were empirically determined and revealed that the springboard stiffness varied appreciably depending upon feet contact position. Given the touchdown kinematics and takeoff angle of the gymnast, the models estimated spring stiffness and linear and angular takeoff velocities, the spring stiffness and takeoff vertical velocity estimates showing some sensitivity to spring angle at touchdown. Simulations in which the touchdown kinematics and spring stiffnesses were systematically adjusted, identified their influence on takeoff kinematics and provided an insight into the mechanics of springboard. contact. Estimated (leg) spring stiffnesses were consistent with those reported in the literature for other activities and'simulation results showed that simple rebounds accounted for the majority of the takeoff velocities. Spring angle at touchdown was found to be most effective at modifying each of the takeoff variables, however to produce a selective effect on takeoff required a combination of adjustments to the touchdown. In proposing strategies for gymnasts, their ability to control each of the touchdown variables has to be considered.